Cyclic Voltammetry of Trazodone as [piperazin-1-yl] Antidepressant Drug and Bovine Serum Albumin Binding - Iffat Azeem,; Shaikh Mohiuddin ,; Arooj Fatima, (Journal of Basic & Applied Sciences, 2016)
The electrochemical behavior of trazodone (TRZ), 2-{3-[4-(3-chlorophenyl)piperazin-1-yl] propyl}-2H,3H-[1,2,4]triazolo[4,3-a]pyridin-3-one has been investigated bycyclic voltammerty measurements at glassy carbon working electrode. The voltammetric method includes selection of supporting electrolyte, pH, scan rate and temperature optimization; and measurements of some other basic voltammetric parameters. The TRZ oxidation peaks are decreased as a result of TRZ-BSA binding. TRZ-BSA binding mechanism is also established.